From bench to bedside: Clinical implications of KRAS status in patients with colorectal liver metastasis. (September 2016) - Andreatos, Nikolaos; Ronnekleiv-Kelly, Sean; Margonis, Georgios A.; Sasaki, Kazunari; Gani, Faiz; Amini, Neda; Wilson, Ana; Pawlik, Timothy M.
Abstract: Introduction: While the role of KRAS in the molecular genetics of colorectal cancer has been studied extensively, its prognostic impact in colorectal liver metastases (CRLM) has only recently been examined. This review aimed to summarize currently reported findings on the clinical implications of KRAS mutant (mut- KRAS ) status for patients with CRLM. Materials and methods: The Pubmed database was searched for relevant articles published from 01/01/2010 to 02/01/2016. Overall survival (OS) and recurrence free survival (RFS) as well as patterns of recurrence were the primary endpoints, but consideration was given to secondary outcomes when the respective findings were of clinical interest. Results: Out of the 266 studies screened, 15 were included in our review. Fourteen studies were retrospective cohorts while one was a systematic review/meta-analysis. Among the 14 retrospective studies, 12 reported OS with 9 detecting a negative association with mut-KRAS status. Similarly, 11 out of 14 retrospective cohorts reported RFS with 6 detecting a negative association with mut-KRAS status. Five studies examined patterns of recurrence, with 4 detecting increased extrahepatic recurrence in the mut-KRAS group. One study examined the different effects of codon-specific KRAS mutations on prognosis. Conclusion: mut-KRAS status predisposes to worse RFS and OS in patients with CRLM, possibly as a result of aggressive tumor biology. Early unresectable extrahepatic recurrence is more frequent in this patient group and may underlie the unfavorable prognosis. Future research should focus on characterizing the distinct effects of codon-specific KRAS mutations as well their interplay with other less common genetic mutations.